2018
DOI: 10.1089/cell.2018.0023
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Functional Myocytes from Equine Induced Pluripotent Stem Cells

Abstract: Induced pluripotent stem cells (iPSCs) have revolutionized human biomedicine through their use in disease modeling and therapy. In comparison, little progress has been made toward the application of iPSCs in veterinary species. In that regard, skeletal myocytes from iPSCs would have great potential for understanding muscle function and disease in the equine athlete. In this study, we generated skeletal myotubes by transducing equine iPSC-derived mesenchymal derivatives with an inducible lentiviral vector codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Furthermore, Aguiar et al[116] showed that eiPSCs could be differentiated into keratinocytes focusing on skin trauma and wound management. Other research groups have studied eventual uses for mesenchymal-like progenitors capable of chondrogenesis and adipogenesis[117] or even induction into functional osteoblasts[118] and transgenic induced myocytes[119], thus providing extra cell sources for regenerative veterinary medicine. Although some studies have already tested the potential and applicability of eiPSCs as seen above, there is still a long road ahead until eiPSCs and their derivatives are completely understood and deemed safe to use in disease models and regenerative veterinary medicine.…”
Section: Horsesmentioning
confidence: 99%
“…Furthermore, Aguiar et al[116] showed that eiPSCs could be differentiated into keratinocytes focusing on skin trauma and wound management. Other research groups have studied eventual uses for mesenchymal-like progenitors capable of chondrogenesis and adipogenesis[117] or even induction into functional osteoblasts[118] and transgenic induced myocytes[119], thus providing extra cell sources for regenerative veterinary medicine. Although some studies have already tested the potential and applicability of eiPSCs as seen above, there is still a long road ahead until eiPSCs and their derivatives are completely understood and deemed safe to use in disease models and regenerative veterinary medicine.…”
Section: Horsesmentioning
confidence: 99%
“…Research on horses is an important aspect of veterinary medicine, particularly in the field of sports medicine, and E-iPSCs for potential injury rehabilitation have been established by our group and many other research teams [7,9,16,25,26]. In this study, E-iPSCs were differentiated into MSCs for cell transplantation to treat musculoskeletal injuries in horses (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their promise for use in veterinary medicine, E-iPSCs have opened up the possibility of using horses for validating stem cell-based therapies before their application in human clinical settings. Research on the differentiation of iPSCs into other cell types, including osteoblasts and myocytes, is ongoing, in efforts to advance the field of regenerative medicine for application to musculoskeletal injuries [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…neural progenitors [41,76,121]), to fully differentiated cell types (e.g. skeletal myocytes [122]). Domestic animal diseases are abundant and have negative health effects for consumers of agricultural animal by-products [123][124][125][126].…”
Section: Tissue and Disease Researchmentioning
confidence: 99%
“…Equine iPSCs (eiPSCs) have been differentiated into several cell and tissue types for disease modelling including neurons [ 86 , 127 ], tendons [ 128 ], myotubes [ 122 ], and osteoblasts [ 129 ]. Functional eiPSC-derived neurons have been produced and were capable of firing action potentials in vitro via functional calcium channels [ 86 ].…”
Section: Tissue and Disease Researchmentioning
confidence: 99%